Bioprinting for bone tissue engineering - Kang, Xin; Zhang, Xiao-Bo; Gao, Xi-Dan; Hao, Ding-Jun; Li, Tao; Xu, Zheng-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
The shape transformation characteristics of four-dimensional (4D)-printed bone structures can meet the individual bone regeneration needs, while their structure can be programmed to cross-link or reassemble by stimulating responsive materials. At the same time, it can be used to design vascularized bone structures that help establish a bionic microenvironment, thus influencing cellular behavior and enhancing stem cell differentiation in the postprinting phase. These developments significantly improve conventional three-dimensional (3D)-printed bone structures with enhanced functional adaptability, providing theoretical support to fabricate bone structures to adapt to defective areas dynamically. The printing inks used are stimulus-responsive materials that enable spatiotemporal distribution, maintenance of bioactivity and cellular release for bone, vascular and neural tissue regeneration. This paper discusses the limitations of current bone defect therapies, 4D printing materials used to stimulate bone tissue engineering (e.g., hydrogels), the printing process, the printing classification and their value for clinical applications. We focus on summarizing the technical challenges faced to provide novel therapeutic implications for bone defect repair.